Biogeographical modules and island roles: a comparison of Wallacea and the West Indies - Carstensen, Daniel W; Dalsgaard, Bo; Svenning, Jens‐Christian; Rahbek, Carsten; Fjeldså, Jon; Sutherland, William J; Olesen, Jens M (Journal of biogeography, 2012)
Aim In order to advance our understanding of the assembly of communities on islands and to elucidate the function of different islands in creating regional and subregional distribution patterns, we identify island biogeographical roles on the basis of the distribution of the islands’ biota within the archipelago. We explore which island characteristics determine island biogeographical roles. Furthermore, we identify biogeographical subregions, termed modules. Location Wallacea in Indonesia, and the West Indies in the Caribbean Sea. Methods We use a network approach to detect island biogeographical roles and avian biogeographical modules. To designate the biogeographical role of an island, each island is assigned two coordinates, l and r. The position of an island in l–r space characterizes its role, namely as peripheral, connector, module hub, or network hub. Island characteristics are tested as predictors of l and r. Results Both Wallacea and the West Indies were found to be significantly modular and divided into four biogeographical modules. The four modules identified within Wallacea each contain all existing island roles, whereas no module in the West Indies represents all possible roles. Island area and elevation appeared to be the most important determinants of an island’s l score, while measurements of isolation essentially determined the r score. Main conclusions In both Wallacea and the West Indies, the geographic structuring into biogeographical modules corresponds well with our knowledge of past connections and contemporary factors. In both archipelagos, large, mountainous islands are identified as hubs and are thus responsible for faunal coherence within modules (module hubs) and across the entire archipelago (network hubs). We thus interpret these as source islands for the surrounding islands in their module (module hubs) or for the entire archipelago (network hubs). Islands positioned marginally in their module and distant from the mainland are identified as connectors or network hubs, behaving as sinks and stepping stones for dispersing species. Modularity and predictors of biogeographical roles are similar for Wallacea and the West Indies, whereas the build‐up of biogeographical modules and the assortment of roles depend on the spatial constellation of islands in each archipelago.